A Comparative Survey on Silicon Based and Surface Acoustic Wave (SAW)-Based RFID Tags: Potentials, Challenges, and Future Directions - Suresh, K. (Institute of Electrical and Electronics Engineers Inc., 2021)
10.1109/ACCESS.2020.2976533